Independensi, Kompetensi, Pelatihan, Pengalaman Kerja, Tingkat Pendidikan dan Kinerja Pengawas Koperasi - Dewi, Putu Ratih Kartika; Yenni Latrini, Made (E-Jurnal Akuntansi, 2020)
The role of supervisors as cooperative internal auditors is very important. Supervisors are tasked with supervising the operations of the cooperative and helping to achieve the goals set by the cooperative. This study aims to determine the effect of independence, competence, training, work experience, and education level on the performance of cooperative supervisors in Buleleng District. The number of samples in this study were 79 respondents. The analysis technique used is multiple linear regression. Research shows that all variables have a positive influence on supervisor performance. This study confirms the  attribution theory. Keywords: Independence; Competence; Training Work Experience; Education Level.